Persons of Interest An Intimate Account of Cecily and John Burton - Burton, Pamela (ANU Lives Series in Biography, 2022)
A world in upheaval; two lives lived under stress ... This story is set in the social and political landscape of pre- and post-World War II. It tells two vastly different tales of Cecily and John's lives in Australia and overseas, as nations clashed, and governments and international organisations tried to remake the world. Cecily Nixon knew that marrying John Burton would be bad for her. But she loved him and, impressed with this handsome, sullen young man and his belief that he could change the world for the better, saw her role in life as to serve the world through John. Cecily's story is a deeply personal and psychological one of love, duty and betrayal that explores the complexities of relationships. In a world that overwhelmed her, Cecily searched for 'wholeness' and delved deep into her psyche to find herself and emerge from John's shadow. John has been known as an influential and controversial young head of Australia's Department of External Affairs - and as a would-be politician. It is less known that he was also an innovative farmer, bookseller, entrepreneur, arts patron and writer. He received international acclaim for his later work in conflict analysis and resolution. These combined stories of courage and achievement unfold amid political intrigue and psychological trauma. ASIO surveillance, love triangles, loyalty, infidelity and tragedy all play their part in the Burtons' lives.